The Concept of Differentiated Learning and Its Implementation in Islamic Education - Tanriveren, Ayse; Azizah, Nurul; Ahyama Afham, Muhammad (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2024)
Differentiated learning has emerged as a critical approach to addressing the diverse learning styles of students. In Islamic education, the need for tailored educational strategies is paramount to achieve holistic development encompassing academic, moral, and spiritual aspects. This research aims to explore the concept of differentiated learning and its implementation in Islamic education, focusing on the impact of different learning styles on student outcomes. This study employs a qualitative approach through library research. Data collection involved comprehensive literature review from books, journal articles, theses, and dissertations. The data were analyzed using thematic content analysis to identify patterns and themes related to differentiated learning and its application in Islamic education. The findings reveal that recognizing and accommodating diverse learning styles—visual, auditory, and kinesthetic—through differentiated instruction significantly enhances student engagement and academic performance. Implementing differentiated learning strategies in Islamic education supports the development of well-rounded individuals. However, challenges such as limited resources and the need for teacher training must be addressed. Educators in Islamic schools should receive adequate training in differentiated instruction techniques. Curriculum development should incorporate flexibility to cater to different learning styles. Further research is needed to explore effective strategies and best practices for implementing differentiated learning in Islamic education contexts.